Electricity market strategies applied to microgrid development - Carlos Ulises Cassiani; John Edwin Candelo Becerra; Fredy Edimer Hoyos (Institute of Advanced Engineering and Science, 2020)
Over the last decade, the liberalization of the electricity market has been sought. In order to fight the environmental impact caused by the use of fossil fuels, it is aimed to change the current system of centralized generation and achieve a more distributed one; distributed resources can use renewable or non-renewable resources as main source of energy, one way to implement these distributed systems is through micro electrical grids, since these allow improving energy efficiency. The way to efficiently implement this type of network is an important point to be solved in future research and even more if the way of conducting an electricity market for different communities is unknown. That is why this text presents the characteristics of microgrids, the management of microgrids, and the wide and promising panorama of future opportunities for a great development of this type of grid.